Економіко-математичні підходи до оптимізації виробничої програми аграрних підприємств - Горобець, Наталія Миколаївна; Gorobets, Natalya; Дьяченко, Ніна Костянтинівна; Diachenko, Nina (My University, 2019)
В статті розглянуто питання моделювання економічних процесів виробничої діяльності сільськогосподарського підприємства. Проведено оптимізацію виробничої структури галузі рослинництва підприємства шляхом економіко-математичного моделювання. Наводяться етапи моделювання виробничих процесів та умови побудови моделі з урахуванням чинників ризику. Обґрунтовано доцільність застосування економіко-математичних методів для вирішення економічних задач в управлінні аграрними підприємствами. Запропоновано введення до сівозміни господарства корисної зернобобової культуру – нут, що забезпечить економічну ефективність за рахунок виходу на нові ринки збуту. На практичному прикладі розглянуто оптимізацію виробничої програми сільськогосподарського підприємства з урахуванням включення до товарного портфелю нішевої культури нут. Розраховано дохід господарства шляхом побудови математичної моделі. За результатами оптимізаційних розрахунків доведено ефективність розподілу посівних площ сільськогосподарських культур та формування оптимальної сівозміни, що забезпечить більшу конкурентоспроможність аграрних підприємств. The article is devoted to the consideration of general aspects of the development of an optimization economic-mathematical model of agricultural resources of agricultural enterprises. Reserves of productive potential, rational use of crop rotation and increase of economic efficiency of economic activity of agro enterprises are revealed. The characteristic conditions and factors that need to be taken into account in the development of a production program are investigated. Applied testing of mathematical calculations has been carried out for an agricultural enterprise that wants to optimize its production structure in order to ensure maximum overall profitability. Such a model can be used to analyze and identify the reserves of resource potential of enterprises of any form of ownership, for different periods of time, as well as to identify the features of strategies for increasing the economic efficiency of economic activity, not only the enterprise as a whole, but also its individual units. In addition, the constructed model can be modified both structurally and substantively. The developed of economic-mathematical model provided for the main types of activities, in particular, the crop industry, namely, the cultivation of cereals and oilseeds. It was established that increasing the profitability of agricultural producers is ensured by optimizing their production structure based on the results of economic and mathematical modeling. The expediency of making further management decisions concerning their economic development and increase of competitiveness of agricultural products on the market is substantiated. According to the results of optimization of the production structure, it is expected to increase the volumes of crop production and increase the proceeds from sales of products. It is established that the construction of optimization of the structure of production will allow to determine the set of basic conditions for the implementation of the economic process in various components of the model. A systematic approach to planning the volumes of crop area of agricultural crops is proposed. The optimal correlation of sown area is established, which will allow to increase the volume of agricultural enterprise production. It has been proved that the process of modeling in the activity of agricultural enterprises enables to make optimal and effective management decisions at different stages of operation and development of the enterprise.
Еconomic and mathematical approaches to optimization of agricultural enterprises 'production program
Н. М. Горобець ORCID ID: 0000G0001G5032G2903 Н. К. Дьяченко ORCID ID: 0000G0002G8506G9204
Keywords: економіко-математичне моделювання; economic-mathematical modeling; оптимізація; optimization; виробнича структура; production structure; нішеві культури; rare cultures; сільськогосподарське виробництво; agricultural production; виробнича програма; production program